Causative factors of cost overrun in highway projects of Sindh province of Pakistan - Sohu, S; Halid, A; Nagapan, Sasitharan; Fattah, A; Latif, I; Ullah, K (IOP Publishing, 2017)
Cost overrun is an increase of cost of project from approved budget which was signed by parties at the time of tender. Cost overrun in construction of highway projects is a common problem worldwide and construction industry of Pakistan is also facing this crucial problem of cost overrun in highway projects of Pakistan. The main objective of this research is to identify the causative factors of cost overrun in highway projects of Sindh province of Pakistan. A well designed questionnaire was developed based on 64 common factors of cost overrun from literature review. Developed questionnaire was distributed among selected 30 experts from owner/client, designer/consultant and contractor who have experience more than 20 years’ experience in highway projects. The collected data was statistical analyzed. After analysis results showed that delay process in payment by client, inadequate planning , client interference, poor contract management, delay of decision making, change of scope of project and financial problems faced by client were most causative factors of cost overrun in highway projects. This research will provide alertness to stakeholders of highway projects of Sindh province to avoid cost overrun in projects.